Age structure and age-related differences in molt status and fuel deposition of Dunlins during the nonbreeding season at Chongming Dongtan in east China - Choi, Chiyeung; Hua, Ning; Gan, Xiaojing; Persson, Christer; Ma, Qiang; Zang, Hongxi; Ma, Zhijun (Journal of Field Ornithology, 2011)
Although most shorebirds exhibit deferred migration and deferred breeding during their first summer, Dunlins (Calidris alpina) migrate to breeding areas and breed during their first summer. First-year and adult Dunlins should, therefore, have similar fueling and molt patterns if energetic and physiological constraints are responsible for deferred migration. From 2006 to 2008, we examined the age structure of Dunlins during the nonbreeding season at Chongming Dongtan, an estuarine wetland in the Yangtze River estuary in east China, and examined the effects of date, age, and molt status on fuel deposition during migration and during the winter. The Dunlin population at Chongming Dongtan was composed primarily of first-year birds. Most adults and first-year birds arrived together in late August. Regression analyses indicated that age, date, and molt status affected fuel deposition (as indicated by body mass) of Dunlins. Adults had significantly greater fuel deposits than first-year Dunlins near the end of northward migration (May: adults 70.8 ± 6.4 g, first-year 63.8 ± 8.0 g) and at the start of southward migration (September: adults 50.2 ± 6.1 g, first-year 47.2 ± 4.9 g). Adults also had significantly higher fuel deposition rates than first-year Dunlins during northward migration. Nonetheless, first-year Dunlins migrate and breed in their first summer. Thus, other factors, such as migration distance and body size, may be more important in determining if first-year shorebirds defer migration during their first spring and summer. During boreal spring and autumn, first-year Dunlins in active body molt had greater body mass than those that had not initiated body molt or those in suspended molt, and premigratory fuel deposits for northward migration were greatest after prealternate molt was completed. These results suggest that body molt requires additional fuel deposits and imposes a constraint on fuel deposition for migratory flights. ©2011 The Authors. Journal of Field Ornithology